Monitoring of wearing and occlusion times with smart shutter glasses—A proof of concept - Ihmig, Frank R.; Januschowski, Kai; Koch, Timo; Velten, Thomas; Rickmann, Annekatrin (PloS one, 2022)
To develop and evaluate an electronic glasses frame for smart liquid crystal shutter glasses that monitors wearing and occlusion times to potentially improve therapy adherence in amblyopia therapy of children. The first generation of an electronic glasses frame for adults was further developed, miniaturized and functionally tested in a proof of concept study on a small group of healthy children. Seven healthy children (4 females, 3 males, 2-9 years) were enrolled in the study. The subjects were instructed to wear the smart shutter glasses and to record their activities in daily life. Averaged and individual results were calculated for the precision of wearing position detection and activity recognition. Also, the proper execution of the configured occlusion pattern was observed. The first generation of an electronic glasses frame for smart liquid crystal shutter glasses in a miniaturized form factor for children. A key element is the implementation of the adaptive shutter operation and of smart algorithms for real-time therapy monitoring. In the proof of concept study, these algorithms monitored the state of wearing position, the wearer's activity and the configured occlusion pattern. The average agreement of the detected states of wearing position was 72.6%. The average activity recognition match was 77.3%. The removal of the glasses was 100% correctly detected and the occlusion was 100% halted when active motion was recognized. The assembled smart shutter glasses for children are suitable for demonstrating the feasibility of continuous therapy monitoring by calculating wearing and occlusion times due to smart algorithms for wearing position detection, activity recognition, and occlusion monitoring. However, further research and studies are necessary to optimize the individual fit and performance of this wearable therapeutic device.